2020
DOI: 10.1177/0883911520973239
|View full text |Cite
|
Sign up to set email alerts
|

Revamping squid gladii to biodegradable composites: In situ grafting of polyaniline to β-chitin and their antibacterial activity

Abstract: The global health concern on wound care is becoming more challenging with the emerging prevalence of inexorable antibiotic resistance. Amidst this crisis, various material innovations have been made to combat this dilemma. Herein, squid pens, which are regarded as discards in the seafood industry, were biorefined into β-chitin-graft-polyaniline (β-chitin-g-PANI) composites for possible wound dressing development. β-chitin was first chemically extracted from gladii, and was then grafted with PANI via in situ ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The BL PAni presents only one endothermic peak at 114 °C. The conventional systems with PAni grafts have copolymer main chain transitions and an exothermic peak at 250 °C corresponding to polymer degradation [ 64 , 65 ]. The BL PAni commences presenting decomposition from 178 °C and degradation to 283 °C, according to the results of the TGA.…”
Section: Resultsmentioning
confidence: 99%
“…The BL PAni presents only one endothermic peak at 114 °C. The conventional systems with PAni grafts have copolymer main chain transitions and an exothermic peak at 250 °C corresponding to polymer degradation [ 64 , 65 ]. The BL PAni commences presenting decomposition from 178 °C and degradation to 283 °C, according to the results of the TGA.…”
Section: Resultsmentioning
confidence: 99%
“…It might, therefore, be utilized as a powerful antibacterial and antistatic agent. Balitaan et al (2020) [ 149 ] synthesized β-chitin-g-PANI composites through the in situ graft copolymerization of β-chitin with conducting PANI. The study findings demonstrated enhanced antibacterial properties, biodegradability, and conductivity in the composites.…”
Section: Applications Of Biodegradable Conducting Polymer Based Compo...mentioning
confidence: 99%
“…16,17 But excessive use of antibiotics may lead to bacterial resistance. 18 As alternatives to antibiotics, various types of metal-based nanoparticles are incorporated into hydrogels to prevent and suppress bacterial infections. 19,20 However, metal-based nanoparticles have potential biological toxicity as they tend to accumulate and spread uncontrollably in the human body.…”
Section: Introductionmentioning
confidence: 99%